Severe and fatal pharmaceutical poisoning in young children in the UK. Issue 7 (16th May 2016) - Anderson, Mark; Hawkins, Leonard; Eddleston, Michael; Thompson, John P; Vale, J Allister; Thomas, Simon H L
Abstract : Objective: Accidental poisoning in young children is common, but severe or fatal events are rare. This study was performed to identify the number of such events occurring in the UK and the medications that were most commonly responsible. Design: Analysis of national data sets containing information relating to severe and fatal poisoning in children in the UK. Data sources: Office of National Statistics mortality data for fatal poisoning; Paediatric Intensive Care Audit Network admissions database and the National Poisons Information Service for severe non-fatal poisoning; Hospital Episode Statistics for admission data for implicated agents. Results: Between 2001 and 2013, there were 28 children aged 4 years and under with a death registered as due to accidental poisoning by a pharmaceutical product in England and Wales. Methadone was the responsible drug in 16 (57%) cases. In the UK, 201 children aged 4 years and under were admitted to paediatric intensive care with pharmaceutical poisoning between 2002 and 2012. The agent(s) responsible was identified in 115 cases, most commonly benzodiazepines (22/115, 19%) and methadone (20/115, 17%). Conclusions: Methadone is the most common pharmaceutical causing fatal poisoning and a common cause of intensive care unit admissions in young children in the UK.